The white princess - Gregory, Philippa (Gregory, Philippa. Cousins' war., 2013)
Passionately in love with Richard III in spite of her arranged marriage to pretender to the throne Henry Tudor, Princess Elizabeth of York is forced to marry the man who murdered her lover and create a royal family under the controlling gaze of his mother, Margaret Beaufort.